A mechanistic evaluation of the traditional uses of Nepeta ruderalis in gastrointestinal and airway disorders - Hassan Mahmood; Mueen Ahmad Chaudhry; Zeeshan Masood; Muhammad Asad Saeed; Sherjeel Adnan (Taylor & Francis Group, 2017)
Context: Nepeta ruderalis Buch.-Ham. (Lamiaceae), locally known as Badranj Boya, is an aromatic herb used traditionally as an antispasmodic, antidiarrhoeal, and anti-asthamatic remedy. Objective: Aqueous methanolic extract of N. ruderalis was studied to investigate its traditional uses. Materials and methods: Study was conducted from September 2015 to February 2016. In vitro spasmolytic and broncho-relaxant activity of crude extract of N. ruderalis (whole plant) was evaluated at 0.01-10 mg/mL final bath concentration in isolated rabbit jejunum and tracheal tissues, using PowerLab data acquisition system (Transonic Systems Inc., Ithaca, NY). In vivo antidiarrhoeal activity was evaluated in castor oil-induced diarrhoeal mice at the dose of 300 and 500 mg of crude extract orally. Results: Crude extract of N. ruderalis completely relaxed spontaneously contracting, high K+ (80 mM) and carbachol (1 μM) induced contracted jejunum with an EC50 value of 5.85 (5.45-6.27), 4.0 (3.80-4.23) and 2.86 (2.48-3.29), similar to verapamil. Nr.Cr relaxed high K+ and carbachol induced contractions, at 5 and 10 mg/mL with an EC50 value of 2.37 (2.11-2.67) and 3.26 (2.9-3.67), respectively, and also displaced calcium concentration-response curves toward right at 0.1 and 0.3 mg/mL. Nr.Cr exhibited antidiarrhoeal protection at a dose of 300 and 500 mg/kg, similar to verapamil, whereas no acute toxicity signs were seen up to 5 g/kg in healthy mice. Discussion and conclusion: Results suggest the presence of spasmolytic and broncho-relaxant effects in the crude extract of N. ruderalis, possibly mediated through calcium channel-blocking activity, providing the pharmacological basis for its traditional uses in gastrointestinal and airway disorders.